Neural Information Processing in Cognition: We Start to Understand the Orchestra, but Where is the Conductor? - Palm, Günther (Frontiers in Computational Neuroscience, 2016)
Research in neural information processing has been successful in the past, providing useful approaches both to practical problems in computer science and to computational models in neuroscience. Recent developments in the area of cognitive neuroscience present new challenges for a computational or theoretical understanding asking for neural information processing models that fulfill criteria or constraints from cognitive psychology, neuroscience and computational efficiency. The most important of these criteria for the evaluation of present and future contributions to this new emerging field are listed at the end of this article.